Dyspepsia: When and How to Test for Helicobacter pylori Infection - Maria Pina Dore; Giovanni Mario Pes; Gabrio Bassotti; Paolo Usai-Satta (Gastroenterology Research and Practice)
Dyspepsia is defined as symptoms related to the upper gastrointestinal tract. Approximately 25% of western populations complain of dyspeptic symptoms each year. 70% of them do not have an organic cause and symptoms are related to the so-called functional dyspepsia, characterized by epigastric pain, early satiety, and/or fullness during or after a meal occurring at least weekly and for at least 6 months according to ROME III criteria. In order to avoid invasive procedures and adverse effects, to minimize costs, to speed up diagnosis, and to provide the most appropriate treatments, primary care physicians need to recognize functional dyspepsia. Because symptoms do not reliably discriminate between organic and functional forms of the disease, anamnesis, family history of peptic ulcer and/or of gastric cancer, medication history, especially for nonsteroidal anti-inflammatory drugs, age, and physical examination could help the physician in discerning between functional dyspepsia and organic causes. For patients without alarm symptoms, noninvasive testing for H. pylori, with either carbon-13-labeled urea breath testing or stool antigen testing, is recommended as a first-line strategy. In this review, we provide recommendations to guide primary care physicians for appropriate use of diagnostic tests and for H. pylori management in dyspeptic patients.